Upaya Meningkatkan Hasil Belajar Siswa Melalui Metode Resitasi dalam Mata Pelajaran PAI Kelas IV SD Negeri 16 Langsat Kadap - Susanti, Devi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve students’ learning outcomes in Islamic Education (PAI) subjects through the application of the recitation method in Grade IV students of SD Negeri 16 Langsat Kadap. The study was motivated by the low student engagement during learning and the high number of students scoring below the Minimum Competency Standards (KKM) due to monotonous teaching methods like lectures. The research was conducted in December 2024, focusing on the topic "Aku Anak Shalih." The results indicated that the recitation method effectively enhanced students’ learning outcomes. Additionally, the study provided insights into applying teaching methods suitable for increasing students’ motivation and understanding of Islamic education subjects. Therefore, the recitation method can serve as an effective alternative in managing the teaching and learning process in Islamic Education.